Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.36
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Modulation for Relation-Level Metaphor Identification

Abstract: Identifying metaphors in text is very challenging and requires comprehending the underlying comparison. The automation of this cognitive process has gained wide attention lately. However, the majority of existing approaches concentrate on word-level identification by treating the task as either single-word classification or sequential labelling without explicitly modelling the interaction between the metaphor components. On the other hand, while existing relation-level approaches implicitly model this interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…First, contextual information is mostly used to enhance the representation of the target word, but the interactions between the target word and its contexts are not explicitly modeled (Zayed et al, 2020;Su et al, 2020). To alleviate this, Su et al (2020) proposed a new paradigm by viewing metaphor detection as a reading comprehension problem, which uses the target word as a query and captures its interactions with the sentence and clause.…”
Section: Formulating Verb Metaphor Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, contextual information is mostly used to enhance the representation of the target word, but the interactions between the target word and its contexts are not explicitly modeled (Zayed et al, 2020;Su et al, 2020). To alleviate this, Su et al (2020) proposed a new paradigm by viewing metaphor detection as a reading comprehension problem, which uses the target word as a query and captures its interactions with the sentence and clause.…”
Section: Formulating Verb Metaphor Detectionmentioning
confidence: 99%
“…Song et al (2020) modeled metaphors as attribute-dependent domain mappings and presented a knowledge graph embedding approach for modeling nominal metaphors. Zayed et al (2020) identified verb-noun and adjective-noun phrasal metaphoric expressions by modeling phrase representations as a context.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Rei et al (2017) proposed a supervised similarity network for relation-level metaphor identification. Zayed et al (2020) introduced a novel architecture for identifying relation-level metaphoric expressions of certain grammatical relations based on contextual modulation, which achieved state-of-the-art results.…”
Section: Metaphor Identificationmentioning
confidence: 99%